Evaluation of antiviral activity of Carica papaya leaves against SARS-CoV-2 assisted by metabolomic profiling. Issue 51 (16th November 2022) - Adel, Amr; Elnaggar, Mohamed S.; Albohy, Amgad; Elrashedy, Ahmed A.; Mostafa, Ahmed; Kutkat, Omnia; Abdelmohsen, Usama Ramadan; Al-Sayed, Eman; Rabeh, Mohamed A.
Abstract : The n -hexane extract showed a significant antiviral activity. In addition, annotated compounds exhibited high binding scores on 6 target viral proteins in silico . Abstract : The COVID-19 pandemic caused a huge health crisis all over the globe. SARS-CoV-2 is the virus responsible for the disease and it is highly contagious leaving millions of confirmed infected cases and a dangerous death toll. Carica papaya is a tropical plant known for its antiviral activity since it possesses different classes of compounds that are believed to combat various viral classes. In this study, the extracts prepared from C. papaya leaves cultivated in Egypt were evaluated for their anti-SARS-CoV-2 activity using crystal violet assay and for their cytotoxicity through MTT assay. The total methanolic extract, n -hexane, ethyl acetate, and n -butanol fractions of papaya leaves were used in the study and the results revealed that the n -hexane fraction has a high anti-SARS-CoV-2 activity with an IC50 value = 1.98 μg mL −1 . Moreover, it also showed a high selectivity index value = 104.7. Dereplication of the secondary metabolites in the crude methanolic extract of C. papaya leaves revealed the presence of different classes of compounds including sterols, terpenes, fatty acid, alkaloids and flavonoids that are known to possess antiviral activities against various classes of viruses. The current study was assisted by molecular docking, molecular dynamics simulation and MM-PBSA calculations for the annotated compounds against 6 SARS-CoV-2 target proteins. The results of these in silico -based investigations showed high to moderate binding on the targeted proteins. This postulation may instigate further research studies concerning the compounds responsible for this high anti-SARS-CoV-2 activity of the n -hexane fraction of C. papaya leaves.